Click Here: Books for ICSE Class 10 Board Exams

Question 1: Find x \ and \  y , if   \begin{bmatrix}  3 & -2 \\ -1 & 4  \end{bmatrix}.\begin{bmatrix}  2x  \\ 1   \end{bmatrix} +2 \begin{bmatrix}  -4  \\ 5   \end{bmatrix}=4 \begin{bmatrix}  2  \\ y   \end{bmatrix}         [2003]

Answer:

\begin{bmatrix}  3 & -2 \\ -1 & 4  \end{bmatrix}.\begin{bmatrix}  2x  \\ 1   \end{bmatrix} +2 \begin{bmatrix}  -4  \\ 5   \end{bmatrix}=4 \begin{bmatrix}  2  \\ y   \end{bmatrix}  

\begin{bmatrix}  6x-2 \\ -2x+4  \end{bmatrix} + \begin{bmatrix}  -8  \\ 10   \end{bmatrix}= \begin{bmatrix}  8  \\ 4y   \end{bmatrix}  

Therefore

6x-10=8 \Rightarrow x = 3  

and -2x+14=4y \Rightarrow y = 2  

Hence x = 3 \ and \ y = 2.   

\\

Question 2: Given \begin{bmatrix}  2 & 1 \\ -3 & 4  \end{bmatrix} . X =  \begin{bmatrix}  7  \\ 6   \end{bmatrix} , find: i) the order of matrix X ii) the matrix X   [2012]

Answer:

\begin{bmatrix}  2 & 1 \\ -3 & 4  \end{bmatrix} . X =  \begin{bmatrix}  7  \\ 6   \end{bmatrix}

A_{2 \times 2} . X_{p \times q} = B_{2 \times 1}

Therefore p = 2 \ and \ q = 1 . Hence the order of Matrix is 2 \times 1 

Let X = \begin{bmatrix}  x \\ y  \end{bmatrix}

Therefore

\begin{bmatrix}  2 & 1 \\ -3 & 4  \end{bmatrix} . \begin{bmatrix}  x \\ y  \end{bmatrix} =  \begin{bmatrix}  7  \\ 6   \end{bmatrix}

\begin{bmatrix}  2x+y  \\ -3x+4y  \end{bmatrix} =  \begin{bmatrix}  7  \\ 6   \end{bmatrix}

Therefore

 2x+y = 7

and -3x+4y = 6

Solving we get x = 2 \ and \ y = 3

Hence X = \begin{bmatrix}  2 \\ 3  \end{bmatrix}

\\

Question 3:  If \begin{bmatrix}  a & 3 \\ 4 & 1  \end{bmatrix}+\begin{bmatrix}  2 & b \\ 1 & -2  \end{bmatrix}-\begin{bmatrix}  1 & 1 \\ -2 & c  \end{bmatrix}=\begin{bmatrix}  5 & 0 \\ 7 & 3  \end{bmatrix}   find the value of   a, b \ and c \    .         [1981]

Answer:

\begin{bmatrix}  a & 3 \\ 4 & 1  \end{bmatrix}+\begin{bmatrix}  2 & b \\ 1 & -2  \end{bmatrix}-\begin{bmatrix}  1 & 1 \\ -2 & c  \end{bmatrix}=\begin{bmatrix}  5 & 0 \\ 7 & 3  \end{bmatrix}  

\begin{bmatrix}  a+2-1 & 3+b-1 \\ 4+1+2 & 1-2-c  \end{bmatrix} = \begin{bmatrix}  5 & 0 \\ 7 & 3  \end{bmatrix}  

\begin{bmatrix}  a+1 & b+2 \\ 7 & -c-1  \end{bmatrix} = \begin{bmatrix}  5 & 0 \\ 7 & 3  \end{bmatrix}  

Therefore

a+1 = 5 \Rightarrow 4  

b+2 = 0 \Rightarrow b = -2  

-c-1=3 \Rightarrow c = -4  

\\

Question 4: If  A =  \begin{bmatrix}  1 & 2 \\ 2 & 1  \end{bmatrix}   , and   B =  \begin{bmatrix}  2 & 1  \\ 1 & 2  \end{bmatrix}  find: i)  A(BA)     ii)  (AB) B.       [1991]

Answer:

i)  A(BA)  

=  \begin{bmatrix}  1 & 2 \\ 2 & 1  \end{bmatrix} [ \begin{bmatrix}  2 & 1  \\ 1 & 2  \end{bmatrix}. \begin{bmatrix}  1 & 2 \\ 2 & 1  \end{bmatrix}]  

=\begin{bmatrix}  1 & 2 \\ 2 & 1  \end{bmatrix}. \begin{bmatrix}  4 & 5 \\ 5 & 4  \end{bmatrix}  

= \begin{bmatrix}  14 & 13 \\ 13 & 14  \end{bmatrix}  

ii) (AB) B  

= (\begin{bmatrix}  1 & 2 \\ 2 & 1  \end{bmatrix} . \begin{bmatrix}  2 & 1  \\ 1 & 2  \end{bmatrix}) . \begin{bmatrix}  2 & 1  \\ 1 & 2  \end{bmatrix}  

= \begin{bmatrix}  4 & 5  \\ 5 & 4  \end{bmatrix} . \begin{bmatrix}  2 & 1  \\ 1 & 2  \end{bmatrix}  

= \begin{bmatrix}  14 & 13 \\ 13 & 14  \end{bmatrix}  

\\

Question 5: Find  x \ and \ y   , if     \begin{bmatrix}  x & 3x \\ y & 4y  \end{bmatrix}. \begin{bmatrix}  2  \\ 1   \end{bmatrix} =  \begin{bmatrix}  5  \\ 12   \end{bmatrix}       [1992, 2013]

Answer:

 \begin{bmatrix}  x & 3x \\ y & 4y  \end{bmatrix}. \begin{bmatrix}  2  \\ 1   \end{bmatrix} =  \begin{bmatrix}  5  \\ 12   \end{bmatrix}  

 \begin{bmatrix}  2x + 3x \\ 2y+4y  \end{bmatrix}. =  \begin{bmatrix}  5  \\ 12   \end{bmatrix}  

Therefore

5x=5 \Rightarrow x = 1 

and 6y = 12 \Rightarrow y = 2 

\\

Question 6: Given A =  \begin{bmatrix}  2 & -1 \\ 2 & 0  \end{bmatrix}   ,   B =  \begin{bmatrix}  -3 & 2  \\ 4 & 0  \end{bmatrix} and C =  \begin{bmatrix}  1 & 0  \\ 0 & 2  \end{bmatrix} ; Find X     such that  A+X=2B+C    .     [2005]

Answer:

 A+X=2B+C   

\begin{bmatrix}  2 & -1 \\ 2 & 0  \end{bmatrix}+X=2\begin{bmatrix}  -3 & 2  \\ 4 & 0  \end{bmatrix}+ \begin{bmatrix}  1 & 0  \\ 0 & 2  \end{bmatrix}    

\begin{bmatrix}  2 & -1 \\ 2 & 0  \end{bmatrix}+X = \begin{bmatrix}  -5 & 4  \\ 8 & 2  \end{bmatrix}     

X = \begin{bmatrix}  -5 & 4  \\ 8 & 2  \end{bmatrix}  - \begin{bmatrix}  2 & -1 \\ 2 & 0  \end{bmatrix}      

X = \begin{bmatrix}  -7 & 5  \\ 6 & 2  \end{bmatrix}    

\\

Question 7: Find the value of x  given that A^2=B ,  A =  \begin{bmatrix}  2 & 12 \\ 0 & 1  \end{bmatrix}   ,   and B =  \begin{bmatrix}  4 & x  \\ 0 & 1  \end{bmatrix} .      [2005]

Answer:

A^2=B

 \begin{bmatrix}  2 & 12 \\ 0 & 1  \end{bmatrix} .  \begin{bmatrix}  2 & 12 \\ 0 & 1  \end{bmatrix}=\begin{bmatrix}  4 & x  \\ 0 & 1  \end{bmatrix}

 \begin{bmatrix}  4 & 36 \\ 0 & 1  \end{bmatrix} = \begin{bmatrix}  4 & x  \\ 0 & 1  \end{bmatrix}

Therefore x = 36

\\

Question 8: If A =  \begin{bmatrix}  2 & 5 \\ 1 & 3  \end{bmatrix}   ,   and B =  \begin{bmatrix}  4 & -2  \\ -1 & 3  \end{bmatrix} and I     matrix of the same order and A^t    is the transpose of the matrix, find A^t.B+BI    .     [2011]

Answer:

A =  \begin{bmatrix}  2 & 5 \\ 1 & 3  \end{bmatrix}  

A^t =  \begin{bmatrix}  2 & 1 \\ 5 & 3  \end{bmatrix}  

A^t.B+BI   

= \begin{bmatrix}  2 & 1 \\ 5 & 3  \end{bmatrix} .  \begin{bmatrix}  4 & -2  \\ -1 & 3  \end{bmatrix}+  \begin{bmatrix}  4 & -2  \\ -1 & 3  \end{bmatrix} . \begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix}   

= \begin{bmatrix}  7 & -1 \\ 17 & -1  \end{bmatrix} +  \begin{bmatrix}  4 & -2  \\ -1 & 3  \end{bmatrix}   

= \begin{bmatrix}  11 & -3  \\ 16 & 2  \end{bmatrix}   

\\

Question 9: Given  A =  \begin{bmatrix}  2 & -6 \\ 2 & 0  \end{bmatrix}   ,   B =  \begin{bmatrix}  -3 & 2  \\ 4 & 0  \end{bmatrix} and C =  \begin{bmatrix}  4 & 0  \\ 0 & 2  \end{bmatrix} ; Find the matrix  X   such that  A+2X=2B+C   .     [2013]

Answer:

A+2X=2B+C  

\begin{bmatrix}  2 & -6 \\ 2 & 0  \end{bmatrix}+2X=2\begin{bmatrix}  -3 & 2  \\ 4 & 0  \end{bmatrix}+\begin{bmatrix}  4 & 0  \\ 0 & 2  \end{bmatrix}  

\begin{bmatrix}  2 & -6 \\ 2 & 0  \end{bmatrix}+2X= \begin{bmatrix}  -6 & 4  \\ 8 & 0  \end{bmatrix}+\begin{bmatrix}  4 & 0  \\ 0 & 2  \end{bmatrix}  

\begin{bmatrix}  2 & -6 \\ 2 & 0  \end{bmatrix}+2X= \begin{bmatrix}  -2 & 4  \\ 8 & 2  \end{bmatrix}  

2X= \begin{bmatrix}  -2 & 4  \\ 8 & 2  \end{bmatrix} -\begin{bmatrix}  2 & -6 \\ 2 & 0  \end{bmatrix} 

X= \frac{1}{2} \begin{bmatrix}  -4 & 10  \\ 6 & 2  \end{bmatrix}

X= \begin{bmatrix}  -2 & 5  \\ 3 & 1  \end{bmatrix}

\\

Question 10: Let A =  \begin{bmatrix}  4 & -2 \\ 6 & -3  \end{bmatrix}   ,   B =  \begin{bmatrix}  0 & 2  \\ 1 & -1  \end{bmatrix} and C =  \begin{bmatrix}  -2 & 3  \\ 1 & -1  \end{bmatrix} . Find A^2-A+BC       [2006]

Answer:

A^2-A+BC  

= \begin{bmatrix}  4 & -2 \\ 6 & -3  \end{bmatrix}.\begin{bmatrix}  4 & -2 \\ 6 & -3  \end{bmatrix}-\begin{bmatrix}  4 & -2 \\ 6 & -3  \end{bmatrix}+\begin{bmatrix}  0 & 2  \\ 1 & -1  \end{bmatrix}. \begin{bmatrix}  -2 & 3  \\ 1 & -1  \end{bmatrix}  

= \begin{bmatrix}  4 & -2 \\ 6 & 3  \end{bmatrix} - \begin{bmatrix}  4 & -2 \\ 6 & -3  \end{bmatrix} + \begin{bmatrix}  2 & -2 \\ -4 & 4  \end{bmatrix}  

= \begin{bmatrix}  2 & -2 \\ -1 & 11  \end{bmatrix} 

\\

Question 11: Let A =  \begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix}   ,   B =  \begin{bmatrix}  2 & 3  \\ -1 & 0  \end{bmatrix} . Find A^2+AB+B^2       [2007]

Answer:

A^2+AB+B^2  

=\begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix}.\begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix}+\begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix}.\begin{bmatrix}  2 & 3  \\ -1 & 0  \end{bmatrix}+\begin{bmatrix}  2 & 3  \\ -1 & 0  \end{bmatrix}.\begin{bmatrix}  2 & 3  \\ -1 & 0  \end{bmatrix}  

=\begin{bmatrix}  1 & 0 \\ 4 & 1  \end{bmatrix}+\begin{bmatrix}  2 & 3 \\ 3 & 6  \end{bmatrix}+\begin{bmatrix}  1 & 6 \\ -2 & -3  \end{bmatrix}  

=\begin{bmatrix}  4 & 9 \\ 5 & 4  \end{bmatrix}  

\\

Question 12: Given A =  \begin{bmatrix}  p & 0 \\ 0 & 2  \end{bmatrix}   ,   B =  \begin{bmatrix}  0 & -q  \\ 1 & 0  \end{bmatrix} and C =  \begin{bmatrix}  2 & -2  \\ 2 & 2  \end{bmatrix} and BA=C^2   . FInd the value of p \ and \ q   .     [2008]

Answer:

BA=C^2  

\begin{bmatrix}  0 & -q  \\ 1 & 0  \end{bmatrix}.\begin{bmatrix}  p & 0 \\ 0 & 2  \end{bmatrix}=\begin{bmatrix}  2 & -2  \\ 2 & 2  \end{bmatrix} .\begin{bmatrix}  2 & -2  \\ 2 & 2  \end{bmatrix}  

\begin{bmatrix}  0 & -2q  \\ p & 0  \end{bmatrix} =  \begin{bmatrix}  0 & -8  \\ 8 & 0  \end{bmatrix}  

Therefore

-2q = -8  \Rightarrow q = 4   

and p = 8   

\\

Question 13: Given A =  \begin{bmatrix}  3 & -2 \\ -1 & 4  \end{bmatrix}   ,   B =  \begin{bmatrix}  6   \\ 1  \end{bmatrix} , C =  \begin{bmatrix}  -4   \\ 5  \end{bmatrix}  and D =  \begin{bmatrix}  2  \\ 2  \end{bmatrix} . Find AB+2C-4D   .     [2010]

Answer:

AB+2C-4D  

 = \begin{bmatrix}  3 & -2 \\ -1 & 4  \end{bmatrix}. \begin{bmatrix}  6   \\ 1  \end{bmatrix} + 2 \begin{bmatrix}  -4   \\ 5  \end{bmatrix} - 4 \begin{bmatrix}  2  \\ 2  \end{bmatrix}  

 = \begin{bmatrix}  16   \\ -2  \end{bmatrix}+\begin{bmatrix}  -8   \\ 10  \end{bmatrix}- \begin{bmatrix}  8  \\ 8  \end{bmatrix}  

 = \begin{bmatrix}  0   \\ 0  \end{bmatrix}  

\\

Question 14: Evaluate  \begin{bmatrix} 4\sin{30^o} & 2\cos{60^o} \\ \sin{90^o} & 2\cos{0^o}  \end{bmatrix} . \begin{bmatrix}  4 & 5 \\ 5 & 4  \end{bmatrix}      [2010]

Answer:

\begin{bmatrix} 4\sin{30^o} & 2\cos{60^o} \\ \sin{90^o} & 2\cos{0^o}  \end{bmatrix} . \begin{bmatrix}  4 & 5 \\ 5 & 4  \end{bmatrix} 

= \begin{bmatrix}  2 & 1 \\ 1 & 2  \end{bmatrix}.  \begin{bmatrix}  4 & 5 \\ 5 & 4  \end{bmatrix}  

= \begin{bmatrix}  13 & 14 \\ 14 & 13  \end{bmatrix}  

\\

Question 15: If A =  \begin{bmatrix}  3 & 1 \\ -1 & 2  \end{bmatrix}   ,   I=  \begin{bmatrix}  1 & 0   \\ 0 & 1  \end{bmatrix} , find A^2-5A+7I   .     [2012]

Answer:

A^2-5A+7I  

= \begin{bmatrix}  3 & 1 \\ -1 & 2  \end{bmatrix}.\begin{bmatrix}  3 & 1 \\ -1 & 2  \end{bmatrix}-5\begin{bmatrix}  3 & 1 \\ -1 & 2  \end{bmatrix}+7\begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix}  

 = \begin{bmatrix}  8 & 5 \\ -5 & 3  \end{bmatrix}-\begin{bmatrix}  15 & 5 \\ -5 & 10  \end{bmatrix}+\begin{bmatrix}  7 & 0 \\ 0 & 7  \end{bmatrix}  

= \begin{bmatrix}  0 & 0 \\ 0 & 0  \end{bmatrix}  

\\

Question 16: If  A =  \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix}, B =     \begin{bmatrix}  4 & 1  \\ -3 & -2   \end{bmatrix} \ and \ C =   \begin{bmatrix}  -3 & 2  \\ -1 & 4   \end{bmatrix}  . Find   A^2 + AC-5B   .     [2014]

Answer:

 A^2 + AC-5B  

 =   \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix}  \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix} +  \begin{bmatrix}  2 & 1  \\ 0 & -2  \end{bmatrix}  \begin{bmatrix}  -3 & 2  \\ -1 & 4   \end{bmatrix} - 5 \begin{bmatrix}  4 & 1  \\ -3 & -2   \end{bmatrix} 

 =   \begin{bmatrix}  4 & 0  \\ 0 & 4  \end{bmatrix}  +  \begin{bmatrix}  -7 & 8  \\ 2 & -8  \end{bmatrix}   -  \begin{bmatrix}  20 & 5  \\ -15 & -10   \end{bmatrix}   =  \begin{bmatrix}  -23 & 3  \\ 17 & 14  \end{bmatrix}

\\

Question 17: Solve for x \ and \ y

i) \begin{bmatrix}  2 & 5  \\ 5 & 2  \end{bmatrix} .  \begin{bmatrix}  x  \\ y  \end{bmatrix} =  \begin{bmatrix}  -7  \\ 14  \end{bmatrix}  

ii) \begin{bmatrix}  x+y & x-4   \end{bmatrix} . \begin{bmatrix}  -1 & -2  \\ 2 & 2  \end{bmatrix} = \begin{bmatrix}  -7  & 14  \end{bmatrix}  

iii) \begin{bmatrix}  -2 & 0  \\ 3 & 1  \end{bmatrix} .  \begin{bmatrix}  -1  \\ 2x  \end{bmatrix} +3 \begin{bmatrix}  -2  \\ 1  \end{bmatrix} = 2 \begin{bmatrix}  y  \\ 3  \end{bmatrix}      [2014]

Answer:

i) \begin{bmatrix}  2 & 5  \\ 5 & 2  \end{bmatrix} .  \begin{bmatrix}  x  \\ y  \end{bmatrix} =  \begin{bmatrix}  -7  \\ 14  \end{bmatrix}  

\Rightarrow \begin{bmatrix}  2x+5y & 5x+2y   \end{bmatrix} = \begin{bmatrix}  -7  \\ 14  \end{bmatrix}  

Therefore

2x+5y = -7  

5x+2y=14  

Solving the above two equations we get

x = 4   and y = -3  

ii) \begin{bmatrix}  x+y & x-4   \end{bmatrix} . \begin{bmatrix}  -1 & -2  \\ 2 & 2  \end{bmatrix} = \begin{bmatrix}  -7  & 14  \end{bmatrix}  

\Rightarrow \begin{bmatrix}  x-y-8 & -2y-8   \end{bmatrix} = \begin{bmatrix}  -7  & 14  \end{bmatrix}  

Therefore

x-y-8=-7 \Rightarrow x-y=1  

Also -2y-8=-11 \Rightarrow y = \frac{3}{2}  

Substituting we get x = \frac{3}{2}+1 = \frac{5}{2}  

iii) \begin{bmatrix}  -2 & 0  \\ 3 & 1  \end{bmatrix} .  \begin{bmatrix}  -1  \\ 2x  \end{bmatrix} +3 \begin{bmatrix}  -2  \\ 1  \end{bmatrix} = 2 \begin{bmatrix}  y  \\ 3  \end{bmatrix} 

\Rightarrow  \begin{bmatrix}  2  \\ -3+2x  \end{bmatrix}  + \begin{bmatrix}  -6  \\ 3  \end{bmatrix} = \begin{bmatrix}  2y  \\ 6  \end{bmatrix} 

 \begin{bmatrix}  -4  \\ 2x  \end{bmatrix} = \begin{bmatrix}  2y  \\ 6  \end{bmatrix} 

Therefore y = -2 and x = \frac{6}{2}=3 

\\

Question 18: If A = \begin{bmatrix}  3 & 5  \\ 4 & -2  \end{bmatrix}   and  B = \begin{bmatrix}  2  \\ 4  \end{bmatrix}  , is the product of AB possible.     [2011]

Answer: 

The order of matrix A = 2 \times 2  and the order of matrix  B \ is \ 2 \times 1 .

Since the number of columns in A  is equal to the number of rows in  B , the product  AB  is possible.

\\

Click Here: Books for ICSE Class 10 Board Exams

Advertisements